Post-weaning performance of calves as affected by longstem hay and method feeding - E.F. Smith; L.H. Harbers (Kansas Agricultural Experiment Station Research Reports, 1971)
Three different rations were compared for feeding calves immediately after weaning. Desired is a ration that will reduce weaning stress, produce economical gains, and be easy to feed. The rations are shown in Table 4. Initial weight of the calves was taken at the pasture just before weaning. The calves were transported the same day 8 miles to the Beef Cattle Research Center where they were divided into groups and started on experimental rations.
Keywords: Cattlemen& #x27; s Day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station); 546; Beef; Performance; Longstem hay; Feeding